2022
DOI: 10.1002/isd2.12256
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms fostering the sustainability of actualized value propositions of implemented e‐Government projects in Sub‐Saharan Africa: A realist evaluation case of Nigeria and Rwanda

Abstract: This study examines the mechanisms fostering sustainable value propositions of implemented e‐Governments projects in sub‐Saharan Africa (SSA) as a research focus. Value propositions identify how public organizations use e‐Government to fulfill citizens' needs across different roles. Using a concept‐centric systematic review, we identified such value propositions as effective public organizations, quality service delivery, open government and democratic values, as well as social values and well‐being. We chose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 201 publications
0
10
0
Order By: Relevance
“…Finally, it can offer valuable feedback and guidance for public sector organisations to assess and enhance their egovernment systems and strategies ( The effectiveness of egovernment systems relies not solely on their technical excellence and functionality but also on how users perceive and appreciate them. The perception of value delivery by egovernment systems among citizens pertains to how they perceive the bene ts outweighing the costs, efforts, time, and risks involved (Chidama & Ononiwu, 2023). Citizens' perception of value delivery by egovernment systems can be in uenced by various factors, like the quality and usability of egovernment systems, including their accessibility, reliability, security, privacy, and user-friendliness (Kervenoael & Yfantis, 2013;Sanghyun et al, 2015).…”
Section: Citizen Perception Of Value Deliverymentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, it can offer valuable feedback and guidance for public sector organisations to assess and enhance their egovernment systems and strategies ( The effectiveness of egovernment systems relies not solely on their technical excellence and functionality but also on how users perceive and appreciate them. The perception of value delivery by egovernment systems among citizens pertains to how they perceive the bene ts outweighing the costs, efforts, time, and risks involved (Chidama & Ononiwu, 2023). Citizens' perception of value delivery by egovernment systems can be in uenced by various factors, like the quality and usability of egovernment systems, including their accessibility, reliability, security, privacy, and user-friendliness (Kervenoael & Yfantis, 2013;Sanghyun et al, 2015).…”
Section: Citizen Perception Of Value Deliverymentioning
confidence: 99%
“…For example, Suradi et al ( 2020) concluded that factors such as usefulness, ease of use, risk, and technology trust were highly valued by Omani citizens while using governmental e-services. Al Rawahi (2019) investigated public value creation through e-government in Oman by adding critical dimensions to the public value creation process and highlighting technology as a distinct dimension (Chidama & Ononiwu, 2023). The study presents a new e-government PV creation model which manifests the knowledge creation process as an ongoing learning process that targets aligning Omani citizens' public value perceptions with an organisation's capabilities (Al Maamari & Bhuiyan, 2021).…”
Section: Oman's E-government Performance International Leapsmentioning
confidence: 99%
See 3 more Smart Citations